2021
DOI: 10.22605/rrh6464
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in a rural health system in New York - case series and an approach to management

Abstract: Introduction: Many rural hospitals and health systems in the USA lack sufficient resources to treat COVID-19. St Lawrence Health (SLH) developed a system for managing inpatient COVID-19 hospital admissions in St Lawrence County, an underserved rural county that is the largest county in New York State. Methods: SLH used a hub-and-spoke system to route COVID-19 patients to its flagship hospital. It further assembled a small clinical team to manage admitted COVID-19 patients and to stay abreast of a quickly chang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…11 Primary healthcare professionals are recommended to be vaccine ambassadors; being trusted sources of factual vaccine information, they can instil confidence in communities, provide credible and trustworthy health information, and discuss fears and safety concerns. 12 In the USA, rural generalist medical professionals were identified as critical to the rural COVID-19 response, 7 were driven by altruism, and were willing to work long hours in the absence of specialists. Additionally, researchers in New Zealand suggested that rural general practices were more adaptive and better able to cope with changed conditions during the COVID-19 pandemic in comparison to urban practices due to their ability to operate in a resource constrained environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Primary healthcare professionals are recommended to be vaccine ambassadors; being trusted sources of factual vaccine information, they can instil confidence in communities, provide credible and trustworthy health information, and discuss fears and safety concerns. 12 In the USA, rural generalist medical professionals were identified as critical to the rural COVID-19 response, 7 were driven by altruism, and were willing to work long hours in the absence of specialists. Additionally, researchers in New Zealand suggested that rural general practices were more adaptive and better able to cope with changed conditions during the COVID-19 pandemic in comparison to urban practices due to their ability to operate in a resource constrained environment.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the USA, rural models of care were developed for vaccination administration and COVID-19 treatment, demonstrating this can be effectively managed by rural health teams and systems. 7 This growing body of research provides important learnings for policy makers for planning a ○ Australia had very high vaccination rates and very low COVID-19 case numbers and deaths in comparison with other countries. 2 Nationally, 42 598 706 COVID-19 vaccine doses had been administered, with 94.4% of people aged over 16 years old having at least one dose and 91.4% being fully vaccinated (defined as having two doses of approved COVID-19 vaccine).…”
Section: Introductionmentioning
confidence: 99%
“…These findings parallel accounts of rural “collaboration and creativity” from the United States, where small communities mobilized the resources available to them, building local capacity to respond to the COVID‐19 crisis. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Rural hospital and primary care services for COVID-19. Rural hospitals, in many cases led by generalists, provided essential health care for mild and moderate cases of COVID-19, taking pressure off higher-level facilities [111][112][113][114]. They faced challenges in operating at the margins at a time when communication channels were disrupted, and support from higher levels was variable, often with limited understanding of the rural hospital context [112].…”
Section: Role Of Digital Technologymentioning
confidence: 99%